High-risk victims of intimate partner violence: an examination of abuse characteristics, psychosocial vulnerabilities and reported revictimization - Tomkins, Jordan (Journal of family violence, 2025)
Purpose: To support service provision, we sought to advance the existing evidence base about the characteristics of—and potential predictors of reported revictimization for—women identified as being at high risk of experiencing ongoing intimate partner violence (IPV). Method: Our sample included 165 high-risk IPV cases with a female victim and a male aggressor managed by the Integrated Safety Response in New Zealand. Based on police and multi-agency risk assessment information, we (a) described the characteristics of these cases, focusing on victims’ abuse experiences and psychosocial vulnerabilities; (b) examined rates of reported recurrence and physical recurrence; and (c) explored which variables predicted these two outcomes across a 12-month follow up, using the Nested Ecological Model as an organizing framework. Results: In addition to experiencing harmful patterns of IPV, victims had relatively high rates of mental health issues, drug use, housing instability and unemployment. Reported revictimization was common: 62.8% of cases involved (at least one) recurrence, and 35.8% of cases involved physical recurrence. Most variables did not predict either outcome, and only two variables consistently predicted rates of recurrence and physical recurrence: strangulation and a victim’s initial engagement with IPV interventions. Conclusions: As predicted, reported revictimization rates were high. Victims also experienced other psychosocial vulnerabilities, confirming their need for wide-ranging support. However, this study raises questions about whether these needs are relevant to predicting reported revictimization within high-risk cohorts, and highlights the difficulties of empirically validating treatment targets that could minimize further IPV harm for this group.